Hyperhomocysteinemia and MTHFR gene 677 C>T polymorphism: questionable role in female infertility - Das, Vinita; Misra, Devyani; Agrawal, Smriti; Agrawal, Anjoo; Pandey, Amita (International Journal of Reproduction, Contraception, Obstetrics and Gynecology, 2017)
Background: Homocysteine is an intermediate in methionine metabolism required for the biosynthesis of nucleic acids. Hyperhomocysteinemia affects various organ systems and also has been implicated as a risk factor for infertility. Elevated levels result either from genetic mutations of the enzymes catalyzing the metabolic pathway or deficiency of micronutrients required as co-enzymes for the same. The aim of this cohort study was to evaluate serum homocysteine levels and MTHFR gene 677C>T mutation and to establish a possible relation between hyperhomocysteinemia, genetic polymorphism and female infertility. Methods: Ninety-five infertile women were enrolled over a period of one year and categorized as unexplained, anovulatory and male partner factor infertility according to the etiology. Thirty-one age-matched fertile women were enrolled as controls. Serum homocysteine levels were evaluated and genetic analysis for MTHFR gene mutation 677C>T was done. Results: Mean homocysteine levels for the women in three infertile groups were comparable (group I - 16.21 ± 3.39 µmol/l, group II - 16.36 ± 3.56 µmol/l, group III - 16.98 ± 3.14 µmol/l) within the groups as well as with the fertile group (15.85 ± 9.3 µmol/l) with no statistically significant difference (P = 0.573). Prevalence of hyperhomocysteinemia was 86.3% for infertile group and 90.3% for fertile group. Nineteen heterozygous (CT) and 3 homozygous (TT) mutations were noted among infertile subjects and 8 heterozygous (CT) mutations among fertile subjects prevalence being similar for both the groups. Conclusions: Significant prevalence of hyperhomocysteinemia and MTHFR polymorphism was observed in the studied population. The study did not establish a positive role of hyperhomocysteinemia and MTHFR mutation in female infertility.